Degradation evaluation index of asphalt pavement based on mechanical performance of asphalt mixture. (1st June 2017) - Gao, Ying; Geng, Dawei; Huang, Xiaoming; Li, Guoqiang
Highlights: Evaluate the degradation of pavement structure with properties of asphalt mixtures. Evaluate the combined effect of climate and traffic load on asphalt pavement. Develop a degradation index to show the aging degree of asphalt mixtures. Abstract: Performance of asphalt pavement degrades after opening to traffic. The degradation of pavement structure is difficult to be evaluated because of the difficulties in in-situ testing and large scattering of testing results. Mechanical properties of asphalt mixtures were tested in this study to indirectly evaluate the degradation of pavement structure. Firstly, different testing methods were discussed from specimen preparation to testing results simulation of pavement structures. Indirect tensile test was finally chosen because of its easy testing process, clear stress state, stable testing results and convenience in preparation of field cored specimen. Secondly, asphalt mixtures with the same material and gradation as that of Nanjing Airport Expressway asphalt pavement were aged from 2 h to 24 h to simulate pavement at different aging period and tested. All testing results are sensitive to aging when the aging time is short and keep relatively stable when the aging time is longer. Elastic modulus of asphalt mixtures is more sensitive to aging time than that of strength and modulus at failure. Degradation Index (Id ) was defined as the ratio of elastic modulus of original asphalt mixture to that of aged mixture which shows the aging degree of asphalt mixtures. Thirdly, fatigue tests were conducted on mixtures of different aging time to determine their fatigue life. Indirect tensile tests were performed on specimens with 20%–80% of fatigue life and different aging time to check the combined effect of climate and traffic loading. Id was modified based on the testing results.